How do Climate and Macroeconomic Factors Affect the Profitability of the Energy Sector? - Joaqui-Barandica, Orlando; Manotas-Duque, Diego F. (International Journal of Energy Economics and Policy, 2023)
This research identifies the significant relationships between climate and macroeconomic variables with the financial profitability (ROA) of energy sector companies in Germany, Norway, France and Spain. We work under the hypothesis of the existence of non-linear relationships for which we fit a Generalized Additive Model (GAM) for each country. We find that macroeconomic variables are often considered more important for modeling profitability than climate variables. This is because general economic conditions, such as interest rates and commodity prices, can have a broader and deeper impact on a firm's financial performance than local climate variations. However, climatic conditions are relevant if the specific industry consists of renewable energy companies. The results of this study can be very useful for financial analysts and investors, as they can adjust their business strategies to improve their financial performance.